Piezoresistive response of extruded polyaniline/(styrene-butadiene-styrene) polymer blends for force and deformation sensors - Teixeira, J. (2018)
Smart materials for sensor applications are increasingly being used in a wide variety of applications ranging from engineering to medical devices. This work reports on piezoresistive sensors based on conductive polyaniline and thermoplastic elastomer processed by conventional polymer extrusion. The material presents excellent processability and piezoresistive performance offering an alternative to traditional composites with conductive nanofillers for sensor applications. The polyaniline/ styrene-butadiene-styrene (PANI/SBS) conductive polymer blends present good mechanical properties, high electrical conductivity and piezoresistive response. The maximum strain reaches ≈60% for 30 weight percentage (wt%) PANI content and the electrical conductivity is σ ≈0.1 S/m for blends with 40 wt% PANI content. Further, the sample with 40 wt% PANI content shows a piezoresistive gauge factor GF ≈1 for deformation measurements between 0.1 to 3 mm in bending cycles.